Pharmacologically Induced Ex Copula Ejaculation in Horses and Donkeys - Khanam, Afroza; Swelum, Ayman A.; Khan, Firdous A. (Frontiers in Veterinary Science, 2021)
Pharmacologically induced ex copula ejaculation is a method used for collection of semen when the traditional methods of semen collection are not feasible. Common indications for this method include health issues that either preclude the physical act of mating or result in impaired erection and ejaculation. The method also offers an alternative when there is a lack of equipment and facilities required for semen collection using the conventional artificial vagina method. A variety of pharmacological protocols for ex copula ejaculation in stallions have been evaluated in both research and clinical settings with no serious side-effects reported. In general, these protocols included tricyclic antidepressants, alpha-2 adrenergic receptor agonists, and smooth muscle stimulators, either individually or in combination. Although there is a lot of variation in the ejaculatory rates among studies, a combination of imipramine and xylazine appears to be an effective option for inducing ejaculation in stallions. In cases where this protocol is not successful, collections should be reattempted using a combination of imipramine, detomidine, and oxytocin. Regardless of the protocol used, a quiet environment with minimal disturbance is associated with a better outcome. In contrast to the body of literature available on pharmacologically induced ex copula ejaculation in horses, only a few studies have been published so far on this topic in donkeys. Further studies are warranted to investigate whether pharmacologically induced ex copula ejaculation is an effective method of semen collection in jacks and to compare different pharmacological protocols for inducing ejaculation in jacks.